Stability of nanocomposites of poly(ε-caprolactone) with tungsten trioxide - Machado, A. V. (2011)
Nanocomposites of poly(ε-caprolactone) (PCL) and tungsten trioxide (WO3) were prepared by solvent casting using 5 and 10% of WO3 nanoparticles. The nanocomposites were characterized using several analytical techniques such as XRD, SEM, thermal analysis (TGA and DSC), spectroscopic methods (FTIR and UV/Vis) to gather information on the modifications introduced by WO3. Photodegradation of PCL/WO3 nanocomposites was studied exposing the samples to a Xenon lamp, which simulates the UV spectrum of the sun. The results obtained showed that due to the incorporation of WO3 nanoparticles, the nanocomposites exhibit higher thermal stability together with higher photodegradation efficiency